ANNUAL MEETING IN RUSSIAN ACADEMY OF AGRICULTURAL SCIENCE, FEBRUARY, 2011 - I.V. Savchenko; A.M. Medvedev (Овощи России, 2011)
On 15-17 February the General Annual Meeting of Russian Academy of Agricultural Science was held where the result of researches for 2006-2010 had been summarized up and new research plan for 2011 was drawn up.